Transition frequencies in the (2-0) band of D2 with MHz accuracy. (September 2020) - Mondelain, D.; Kassi, S.; Campargue, A.
Highlights: The S (0) and Q (1)- Q (4) transitions of the very weak (2-0) band of D2 are measured. The Q (3) and Q (4) transitions are observed for the first time. Multi-spectrum treatment with a quadratic speed-dependent Nelkin-Ghatak profile. MHz position accuracy by CRDS linked to a Rb clock referenced comb. Positions and intensities agree with the latest ab initio calculations. Abstract: Series of spectra of the S (0) and Q (1)- Q (4) transitions of the (2-0) band of D2 near 5860 cm −1 are recorded by comb-referenced cavity ring down spectroscopy, at four pressures up to 200 Torr. After averaging, high resolution (30 MHz step) and low noise (noise equivalent absorption, αmin ≈ 1.5 × 10 −11 cm −1 ) spectra are obtained for each pressure value. This leads to signal to noise ratios of several hundred for the considered very weak electric quadrupole transitions with intensities ranging between 4 × 10 −29 and 4 × 10 −28 cm/molecule. The Q (3) and Q (4) transitions are newly detected. A multi-spectrum treatment of the D2 line profiles at different pressures performed using a quadratic speed-dependent Nelkin-Ghatak profile leads to residuals close to the noise level. Considering statistical fit errors and possible biases, total uncertainties on the frequencies extrapolated at zero pressure are estimated to be between 0.30 MHz and 1.83 MHz. The derived experimental frequencies and intensities of (2-0) transitions are gathered with literature values and compared to ab initio values reported in J. Komasa, M. Puchalski, P. Czachorowski, G. Łach, K. Pachucki, Phys. Rev. A 100, 032519 (2019) . An agreement within the combined uncertainties is achieved for the S (0), Q (1), Q (2) and Q (3) transitions. Line intensities are also discussed in relation with literature values. Graphical abstract: Image, graphical abstract